A case of complete atrioventricular block associated with primary cardiac lymphoma reversed without cardiac pacemaker implantation. Issue 4 (April 2022) - Hu, Bowen; Zhao, Jian; Liang, Xin; Ren, Changzhen; Li, Na; Liang, Chun
Primary cardiac lymphoma (PCL) is a rare malignant lymphoma that is characteristically confined to the heart and/or pericardium. Here, the case of a 70-year-old male patient with complete atrioventricular block (AVB) associated with PCL is presented. The patient had a 10-month history of palpitation and electrocardiogram (ECG) showed a complete AVB. Additionally, transthoracic echocardiography indicated pericardial effusion where atypical lymphoid cells were identified by pericardiocentesis. Subsequent mediastinal lymph node biopsy revealed non-germinal centre diffuse large B-cell lymphoma. Therefore, a diagnosis of PCL was confirmed. As the patient's vital signs were stable, he was prescribed chemotherapy without pacemaker implantation. After chemotherapy, the patient achieved remission and dynamic ECG demonstrated no recurrence of AVB. The present case demonstrates that although PCL initially manifesting as complete AVB is rare, this possibility should not be ignored when a new AVB without definite aetiology is encountered. In addition, if the vital signs of the patient are stable, pacemaker implantation may be postponed until the treatment effect of chemotherapy has been assessed.